Issues on the use of online learning: An exploratory study among university students during the COVID-19 pandemic - Ilias A.; Baidi N.; Ghani E.K.; Razali F.M. (Horizon Research Publishing, 2023)
Online learning has become important to most students and lecturers in this academic era due to the COVID-19 Pandemic. This study attempted to investigate issues pertaining to online learning among university students in Malaysia during this pandemic. The online interview technique used various online platforms involving 147 students from 16 universities in Malaysia. Data from the interview were analysed using ATLASti. Findings indicated that there are seven challenges that might limit the intention to use online learning among students. The challenges outlined are the administrator's assessment, communication issues that limit social interaction during online learning sessions, technical issues as well as an unstable Internet connection and insufficient data capacity. This study could contribute to the existing corpus of knowledge that could help universities to strategize the future implementation of online learning and minimize the challenges. This could improve the intention and preferences to use online learning for future implementation. Copyright 2020 by authors.